The relationship between illness representations, coping and quality of life among patients undergoing haemodialysis in Malaysia's NGO-based haemodialysis centres - Fatanah Ramlee (Tanjong Malim, 2012)
The relationship between illness representations, coping and quality of life among patients undergoing haemodialysis in Malaysia's NGO-based haemodialysis centres by Fatanah Ramlee